Impact of melatonin receptor‐signaling on Zeitgeber time‐dependent changes in cell proliferation and apoptosis in the adult murine hippocampus. Issue 5 (2nd February 2017) - Fredrich, Michaela; Hampel, Mareike; Seidel, Kay; Christ, Elmar; Korf, Horst‐Werner
ABSTRACT: The hippocampus is subjected to diurnal/circadian rhythms on both the morphological and molecular levels. Certain aspects of cell proliferation in the adult hippocampus are regulated by melatonin and accompanied by apoptosis to ensure proper tissue maintenance and function. The present study investigated Zeitgeber time (ZT)‐dependent changes in cell proliferation and apoptosis in the adult murine hippocampus and their regulation by melatonin receptor type1 and type2 (MT1/2)‐mediated signaling. Adult melatonin‐proficient C3H/HeN mice and melatonin‐proficient (C3H/HeN) mice with targeted deletion of MT1/2 were adapted to a 12‐h light, 12‐h dark photoperiod and were sacrificed at ZT00, ZT06, ZT12, and ZT18. Immunohistochemistry for Ki67 and activated caspase‐3 in combination with different markers for the diverse cell types residing in the hippocampus served to identify and quantify proliferating and apoptotic cells in the hippocampal subregions. ZT‐dependent changes in cell proliferation and apoptosis were found exclusively in the subgranular zone (SGZ) and granule cell layer (GCL) of melatonin‐proficient mice with functional MT1/2. Cell proliferation in the SGZ showed ZT‐dependent changes indicated by an increase of proliferating immature neurons during the dark phase of the 24‐h light‐dark cycle. Apoptosis showed ZT‐dependent changes in the SGZ and GCL indicated by an increase of apoptotic immature neurons at ZT06 (SGZ) and a decrease of immature and mature neurons at ZT18 (GCL). Our results indicate that ZT‐dependent changes in proliferation of immature neurons in the SGZ are counterbalanced by ZT‐dependent changes in apoptosis of immature and mature neurons in the SGZ and GCL exclusively in mice with functional MT1/2. Therefore, MT1/2‐mediated signaling appears to be crucial for generation and timing of ZT‐dependent changes in cell proliferation and apoptosis and for differentiation of proliferating cells into neurons in the SGZ. © 2017 Wiley Periodicals, Inc.